Laboratory Investigation of Behavioural Changes in Tensile Strength of Bituminous Concrete Mixes Subjected to Differential Loading Temperature - Aleruchi Igwe, Enwuso; Nyebuchi, Daniel Azeruibe (IJRDO - Journal of Mechanical And Civil Engineering, 2017)
This paper presents a laboratory investigation of the behaviour of bituminous concretemixtures when subjected to differential loadings in temperature with respect to tensilestrength. The study became necessary because previous works have revealed that bitumenwhich is the binding agent in bituminous concrete can easily flow or flush under increasedtemperature causing separation from aggregates. For the present study, laboratory specimensof bituminous concretes were prepared in accordance with specified standards and twoindirect tensile testing methods (split cylinder and double punch tests) were used to evaluatethe behavioural changes in tensile strength that occurred. The laboratory procedure involvedtesting the specimens under increasing temperature of loading between 20°C - 60°C withincremental loadings of 10°C. The study was carried out for three categories of traffic –Light, Medium and Heavy traffic categories respectively. The results obtained revealed thatincrease in mix temperature of asphalt/bituminous concretes from 20°C - 60°C adverselyaffected the tensile strength behaviour of the concrete under external traffic loading.Furthermore, results of tensile strength from the double punch test were better than thosefrom split cylinder test for all categories of traffic under varying temperature between 20°C -60°C.